2023
DOI: 10.1186/s40359-023-01059-9
|View full text |Cite
|
Sign up to set email alerts
|

Depression and quality of life among Afghan healthcare workers: A cross-sectional survey study

Abstract: Background According to the World Health Organization, approximately 280 million individuals worldwide suffer from depression. One occupational group that is more prone to mental health issues is healthcare workers (HCWs). However, very little is known about the mental health of HCWs in Afghanistan. Therefore, the present study examined depression, quality of life (QOL), and related factors among Afghan HCWs. Methods A cross-sectional survey was a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These ndings are novel as no previous study in Afghanistan has assessed the prevalence of stress among the general population. However, studies have been conducted on the mental health of healthcare workers [39], adolescents [40], and women in Afghanistan [22]. These results diverge from those of a systematic review conducted by Salari et al among general population [41], which identi ed a negative association between stress and the age group of participants (n = 9074).…”
Section: Discussionmentioning
confidence: 66%
“…These ndings are novel as no previous study in Afghanistan has assessed the prevalence of stress among the general population. However, studies have been conducted on the mental health of healthcare workers [39], adolescents [40], and women in Afghanistan [22]. These results diverge from those of a systematic review conducted by Salari et al among general population [41], which identi ed a negative association between stress and the age group of participants (n = 9074).…”
Section: Discussionmentioning
confidence: 66%
“…10 A recent study from Afghanistan found HCWs who reported a low monthly income to be at higher risk of depression than those in higher wage brackets. 11…”
Section: Financial Concerns and Their Association With Depressionmentioning
confidence: 99%
“…Additionally, those with a higher quality of life were less susceptible to depression. 46 COVID-19 resilience was found to be a risk factor for developing both anxiety and depression, while self-esteem and social support were protective factors against both. The outbreak of COVID-19 disrupted the routine work and personal lives of healthcare workers.…”
mentioning
confidence: 94%